The Revitalization Model Through the Implementation of Accounting Information System for Village Unit Cooperative in Banyumas Region, Indonesia - Eko Suyono; Oman Rusmana; Riswan Riswan (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2019)
One of the obstacles faced by the Village Unit Cooperative (VUC) in dealing with the current competitive business environment is the limited resources both in term of funds and infrastructure. Meanwhile, modern business is supported by the large scale of resources such as modern infrastructure, professional human resources, and extensive networks both at national and international levels. This study tries to evaluate the information system needs by VUC in order to sustain their business both manual and computer-based accounting system. The data was collected through in-depth interview, observation, and focus group discussion during community engagement activity conducted from July to October 2018. By using 6 VUCs in Banyumas as a sample, this study documents the steps in system development by using system development life cycle such as provide general information of the business, a summary of accounting policies, account guidelines and financial statements format, description of account codes, and the forms or the standards of journal entries. Moreover, this study designs a computer-based accounting system by using the Pivot Table on Microsoft Excel. With the good supervision in implementing all steps in system development, it is expected that the VUCs in Banyumas will be more sustainable and professional in managing their business in a very competitive business environment.